Uji Biologis Berbagai Formula Pakan Ayam Petelur Menggunakan Maggot BSF - Purnamasari, Dwi Kusuma; Wiryawan, I.K.G.; Sumiati, Sumiati; Erwan, Erwan; Maslami, Vebera; Ramadhan, I.P.; Islam, L. Azan (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Research on using maggots as a feed ingredient for laying hens is one solution to the problem of increasing feed prices and BSF maggots also have the potential to overcome environmental problems caused by the accumulation of organic waste. The research was carried out in 3 stages, namely: Stage 1. Macronutrient chemical testing of all ingredients to be used in the feed formula for laying hens. Stage 2. Preparation of 3 feed formulas using bran, corn, concentrate, and maggot according to the needs of layer phase laying hens. Stage 3. Biological testing of 3 feed formulas for 120 chickens divided into 3 treatments and 4 replications consisting of 10 chickens, according to a Completely Randomized Design. The parameters observed were feed consumption, egg weight, egg production, FCR, and egg quality both external and internal. The collected data will be tabulated and Analysis of Variance (ANOVA) and Duncan’s Multiple Range Advanced Test will be carried out. This research shows that giving up to 30% maggot was not able to produce better feed consumption, egg weight, egg production, and feed conversion compared to the control. However, based on an analysis of the internal quality of the eggs, the treatment with 30% maggot was able to produce eggs with a high yolk score (9.70±0.66) and was significant compared to the control (8.30±0.75). The conclusion from this research is that maggots have the potential to be used as feed for laying hens up to a level of 30%.